Elementary School Recruitment New Student Management(A Site Study at SDN Kemirirejo Magelang) - PURWANTO , PURWANTO (2011)
The objectives of this research is to describe (1) the registration of new students at SDN Kemirirejo 3 Magelang. (2) The selection activity of new students recruitment at SDN Kemirirejo 3 Magelang. (3) Publication of new students recruitment result at SDN Kemirirejo 3 Magelang. This is a qualitative and used an ethnographic design. This research was conducted on SDN Kemirirejo 3 Magelang. The main subject of research is the Principal, New Student Recruitment Committee of SDN Kemirirejo 3 Magelang. Data collection methods used in depth interviews, participatory observation, and documentation. Analyses of data used data analysis model are arranged in a site. The validity test of data used credibility, transferability, conformabilities and dependability. The results of this research are (1). Enrollment activities of new students at SDN kemirirejo 3 Magelang is managed by the New Student Recruitment committee that established by the Decree of principal. The chronology of registration is begins with filling the form, and submission of birth certificate file and certificate awards. SDN Kemirirejo 3 Magelang does not charge a registration fee for the recruitment activities because it is financed by the coordination of Education Magelang. The prospective students who have completed registration documents will get a card that is used for selection tests in the next day. (2) The acceptance selection of new student in SDN Kemirirejo 3 Magelang is done with three types of selection that is administration, practices, and also interview selection. The content of assessment in the selection includes age, residency, language preparedness, readiness arithmetic, personality, religion, and also the charter. Results of selection are announced at the announcement board in summary form of selection test scores that have been ranked by new student recruitment committee at SDN Kemirirejo 3 Magelang. (3) Results publication of new student's acceptance at SDN Kemirirejo 3 Magelang is done directly at the school through the installation of the recapitulation of the selection on the bulletin board. School does not publish through electronic media such as radio or website or print media such as newspapers. Recapitulation of the value of selection is the accumulation value of material evaluation that is made with assessment ratings by the new student recruitment committee. For students who pass the selection, they can do the re-registration.